PFO closure in high-risk patient with paradoxical arterial embolism, deep vein thrombosis, pulmonary embolism and factor V Leiden genetic mutation. Issue 3 (14th March 2018) - Parikh, A; Vacek, T P
Abstract: Occurrence of paradoxical arterial embolism may cause the first symptoms in patients with a coexisting hypercoagulable state and patent foramen ovale (PFO). This can result in significant morbidity and mortality depending on the location of the embolism. The risks and benefits of closure of small PFOs have not been well elucidated in prior studies. We describe a patient with a history of Factor V Leiden heterozygosity who presented with left arm pain secondary to arterial embolism. The patient was a 51-year-old male who initially presented to the emergency department after awaking from sleep with progressive, severe, burning left arm pain. He had also noted intermittent shortness of breath over the 2 weeks prior to admission. Temperature was 97.4 F, pulse 86, respiratory rate 20 and blood pressure 121/87. Oxygen saturation was 94% on supplemental oxygen. He had a cool left upper extremity and the patient described subjective paresthesias in this extremity. Left radial pulse was difficult to palpate. Physical exam was otherwise unremarkable. Troponin I was mildly elevated at 0.217 ng/l. White blood cell count was 11.8 and INR 1.1. EKG showed sinus tachycardia with non-specific T abnormalities in the anterior leads. His past medical history was notable for only hypertension and hyperlipidemia. Current recommendation is for antiplatelet or anticoagulation for those with hypercoaguable states who suffer a stroke; there is currently no absolute indication for closure device. We describe the case of a 51-year-old male who had presented with left arm pain and shortness of breath. The computed tomography (CT) angiography of chest showed pulmonary emboli with heavy clot burden bilaterally. Heparin was started, but patient was found to have occlusion along large arteries of the left arm. Emergent left axillary, brachial, radial and ulnar embolectomy for acute critical arm ischemia were performed. The transthoracic echocardiogram done the next day with bubble study was positive for patent foramen ovale. Hypercoaguability showed factor V Leiden heterozygosity. Decision was made for the patient to initiate long-term anticoagulation with rivaroxaban and closure was performed. Patient was advised that closure is off label but opted to proceed with closure in light of hypercoaguable state.